Advanced catalyst design induced enhancement of multi-walled nanotube debundling and electrical conductivity of multi-walled nanotube/silicone composites. Issue 53 (16th May 2016) - Lee, Sang-Eui; Cho, Shinje; Kim, Hajin; Han, Intaek; Sohn, Yoonchul
Abstract : Density of MWNT bundles can be controlled by synthetic process of metal catalysts. Direct correlation between morphology of MWNT catalysts and electrical conductivity of MWNT/polymer composite was experimentally demonstrated. Abstract : Multi-walled nanotube (MWNT)/silicone composites were fabricated with two different kinds of MWNT bundles grown by catalysts with different morphology. The order of agglomeration of MWNTs turned out to be closely related to the shape of the catalyst particles. Though the same composition of precursors was used, catalyst particles made from gelation of the precursors followed by flame synthesis (FS) consisted of chunk-type particles, while those from spraying of the precursor solution followed by thermal decomposition (STD) were fabricated with the shape of thin sheets. After CVD growth, the MWNT bundles were entangled to form large masses for FS-catalysts but they maintained rod-like morphology for STD-catalysts. Individual bundles of the STD-MWNTs also contained a smaller population of MWNTs with more room inside, which finally resulted in highly conductive MWNT/silicone composite due to effective dispersion of the MWNTs. In this study, for the first time, direct correlation between morphology of MWNT catalysts and electrical conductivity of MWNT/polymer composites was experimentally demonstrated and a high electrical conductivity of 1407 S m −1 was acquired using a mass production compatible three roll milling process.